(untitled) (Annals of Medical Research, 2021)
Aim: Cholangiocellular carcinomas are rare bile duct tumors. They are categorized as intrahepatic(iCCA), perihilar(pCCA) or distal(dCCA) cholangiocarcinomas according to their anatomical location. In this study, we aimed to present our clinical experience in patients with cholangiocellular carcinoma. Material and Methods: Patients who underwent curative surgery with the diagnosis of cholangiocellular carcinoma between 2010 and 2019 were retrospectively reviewed. Demographic and clinical characteristics, surgical procedures, tumor characteristics, short- and long-term results and survival of the patients were analyzed.Results: Twentynine patients were included in the study. The mean age of the patients was 63.3(±10.8) years, and 52% of the patients were older than 65 years. Male sex was 79.3%. Percutaneous biliary drainage was performed in 52% of the patients before the operation. Tumor localizations were distal (dCCA) in 12 (41.4%) patients, perihilar (pCCA) in 11 (38%) patients, and intrahepatic (iCCA) in 6 (20.6%) patients. Only biliary resection was performed in 69%, hepatic + biliary resection in 27.6%, and only hepatic resection in 3.4% of the patients. The mean tumor size was 3.08 cm (±1.91), tumor stage was commonly stage II (58.6%) and postoperative complication was seen in 13.8% of the patients. Ninety-day unplanned readmission was observed in 31.3%, postoperative mortality in 6.9%, and recurrence during postoperative follow-up in 24.2% of the patients. The mean survival time was 22.82(±13.72) months. Conclusion: The type of surgical approach to be performed in cholangiocellular carcinoma is related to the localization of the tumor. With the right patient selection, curative surgical treatment can be performed at low morbidity and mortality rates.